Predictors of Adverse Cardiovascular Events After CABG in Patients with Previous Heart Failure - Alla Garganeeva; Elena Kuzheleva; Olga Tukish; Michail Kondratiev; Karina Vitt; Sergey Andreev; Yury Bogdanov; Oksana Ogurkova (Life)
Coronary artery disease (CAD) is the primary risk factor for heart failure (HF) development. Coronary artery bypass graft (CABG) surgery remains the gold-standard treatment for multivessel coronary artery disease. The purpose of this study was to identify predictors of cardiovascular events in patients after CABG by looking at clinical parameters, examining biomarkers of inflammation and fibrosis, and assessing patients’ adherence to heart failure therapy before CABG. The prospective observational study included consecutively hospitalized patients with HF and CAD eligible for CABG (n = 82). The study’s primary endpoint was a combination (MACE) of cardiac death, hospitalization with HF, acute ischemic events requiring unplanned revascularization, or stroke. The enzyme-linked immunosorbent assay was performed to assess serum levels of NGAL, GDF-15, NTproBNP, TGF beta, and hsCRP. The participants’ medication adherence level was assessed using the Morisky–Green scale. A total of 37 events were registered (45.1%) at follow-up (36 (26; 43) months). All patients were divided into two groups: Group 1 (n = 45) comprised patients without the combined endpoint, and Group 2 (n = 37) comprised patient who suffered adverse cardiovascular events. A high GDF-15 level and low adherence based on the Morisky–Green scale were independent predictors of a MACE at follow-up. The median time before the development of the MACE which was predicted based on Kaplan–Meier analysis in the group with a GDF-15 value less than 2064 pg/mL was 64 (50; 80) months, and in the group with a GDF-15 value more than or equal to 2064 pg/mL, it was 40 (34; 46) months (p < 0.001). Higher GDF-15 values and poor adherence to treatment are associated with adverse cardiovascular events in patients with HF and CAD who have undergone CABG. However, further studies are needed to support the use of GDF-15 as a prognostic marker in real-life clinical practice.